Poly(2‐isopropyl‐2‐oxazoline) Bearing a Spiropyran Side‐Chain: Synthesis and Evaluation of Photo and Temperature‐Responsive Properties. Issue 22 (19th November 2019) - Machida, Shinjiro; Nakamura, Yuta; Itaya, Akira; Ikeda, Noriaki
Abstract : Front Cover : In article number 1900240 by Shinjiro Machida and co‐workers, photo and temperature‐responsive poly(2‐isopropyl‐2‐oxazoline)s with a spiropyran group in the side‐chain are synthesized, and their stimuli‐responsive properties in aqueous solution are evaluated. The introduction of spiropyran groups causes a marked decrease in the cloud point of the aqueous solution even when the pendant groups contain the zwitterionic merocyanine form. The photoinduced phase transition is demonstrated at an optimum temperature.